A mad tea-party: spread - Favre, Chelsea (My University, 2021)
In “A Mad Tea-Party from Alice’s Adventures in Wonderland’’ by Lewis Carroll, Alice has just met the Mad Hatter, March Hare, and the Dormouse at their tea-party, where she engages in a nonsensical conversation regarding hair cutting, riddles, buttered clocks and time. The Hatter chimes in periodically with off-topic chatter that derails the conversation at hand, much to the annoyance of Alice. Her consternation grows more apparent as the conversation continues, and it ends with a nonsensical parody of Twinkle Twinkle Little Star. A whimsical approach was taken in the way the text is laid out on the page, aiming to lead the reader’s eye down a winding, amusing path from one section to the next. The Hatter’s nonsensical interruptions break the text using a larger coloured and eccentric typeface to accentuate how disruptive his interruptions are. Despite the interjection of the larger text into the normal paragraphs, they are presented in a way that leads to the next part of the story with ease. Alice’s irritation is expressed in red with certain words emphasized in larger, bolder text to force that annoyance on the reader, growing in size to match her growing irritation as the story progresses. The illustrations used to decorate this piece add to the whimsical, fantastical nature of the story. The little Mad Hatter hat that sits upon the first letter of the story draws attention to the beginning, while the teapot pouring tea down the text into a much larger teacup below not only helps the reader navigate the text but also brings attention to the setting of the story. The image serves to illustrate how bizarre the world is that Alice finds herself in. Lastly, the image of a sleepy Dormouse brings attention to the ending of the tale, providing a delightful, visual element to the conclusion. Course: DESN 231 Typography II.
Keywords: typography; layout